Participation in daily life of people with schizophrenia in comparison to the general population: Comparaison de la participation à la vie quotidienne des personnes atteintes de schizophrénie à celle de la population générale. (December 2016) - Lipskaya-Velikovsky, Lena; Jarus, Tal; Easterbrook, Adam; Kotler, Moshe
Background: Participation in occupations is a basic human right. Although people with schizophrenia commonly experience restrictions in participation, there is a paucity of research in this area. Purpose: This study aimed to compare the participation patterns of people with schizophrenia to people without mental illness (control group). Method: A total of 140 people of similar age and sex completed the Adults Subjective Assessment of Participation and provided demographic and health-related data. Findings: People with schizophrenia tend to participate in fewer activities and to participate alone. However, they participate with similar intensity as those in the control group. Implications: The participation patterns of people with schizophrenia are both unique and similar to those of the general population. The differences in participation raise concerns due to signs of restriction and social exclusion. However, it appears that people with schizophrenia benefit from occupation and community-based services that promote and support participation with others in diverse activities.